Case report: A severe case of zoledronate-associated diffuse orbital inflammation and uveitis in a patient with metastatic breast cancer - Kanda, Pushpinder; Guerrero-Córdova, Isaura; Dhillon, Jobanpreet; Tsang, Adrian (Frontiers in Ophthalmology, 2024)
IntroductionZoledronate is a commonly prescribed medication to maintain bone health; however, a rare side effect includes ocular inflammation. We report a case of simultaneous anterior uveitis and orbital inflammation associated with zoledronate infusion in a patient with metastatic breast cancer. We also performed a literature search to provide an up-to-date summary of cases with zoledronate-associated ocular inflammation.MethodsThis is a case report with literature review. Literature search (timeline 2010 to 2023) was performed using PubMed with the search team: (zoledronate) AND (uveitis OR scleritis OR orbital inflammation OR ocular inflammation).ResultsA 48-year-old female presented with left eye pain, swelling, and decreased vision 2 days after receiving zoledronic acid infusion. An ophthalmic exam showed non-granulomatous anterior uveitis. CT orbits and ocular ultrasound showed signs of posterior scleritis and orbital inflammation. Ocular inflammation caused by an infection or metastatic cancer was ruled out. The patient was treated with both topical and systemic corticosteroids. Complete resolution of the inflammation occurred after 2.5 weeks.ConclusionOrbital inflammation and uveitis are an uncommon side effect of zoledronate but needs to be promptly recognized and treated to prevent sight-threatening complications.